The Rise of Indonesia Diplomatic Power - Deliana, Nia (Muslim Politics Review, 2022)
Indonesia’s a Foreign Policy and Grand Strategy in the 21st Century: Rise of an Indo-Pacific Power. Vibhanshu Shekhar. Routledge, Taylor and FrancisNumerous experts have pointed out the changing nature of global order in the twenty-first century. As one of the world’s middle powers, Indonesia has been claiming the title of the rising power in the Indo-Pacific region through upgrading its foreign policies and attitudes in international relations. To look further into the realities, challenges, and prospects of Indonesia’s shifting foreign policy and projection of its global strategy, Vibhanshu Shekhar has authored a 250-page book of six chapters that concentrates on three keys elements: Indonesia’s emerging power, status signalling, and the Indo-Pacific region.